2022
DOI: 10.3390/vaccines10030430
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Real-World Vaccination Effectiveness of mRNA COVID-19 Vaccines against Delta and Omicron Variants in Japan

Abstract: A resurgence of COVID-19-positive cases has been observed in many countries in the latter half of 2021. The primary reasons for this resurgence are the waning immunity of vaccination after the second dose of vaccination and the changes in public behavior due to temporal convergence. The vaccination effectiveness for the omicron and delta variants has been reported from some countries, but it is still unclear for several other regions worldwide. Here, we numerically derived the effectiveness of vaccination for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…The included studies had a total sample of around one hundred million (N = 148260342) participants and of these, 74.2% were fully vaccinated ( n = 110076947) with at least two-doses of COVID-19 vaccines ( Table 1 ). Among the 13 studies, 1 study reported the effectiveness of the BNT162b2 (Pfizer–BioNTech), ChAdOx1 (AstraZeneca), mRNA-1273 (Moderna) and JNJ-78436735 vaccines ( 25 ); 1 study reported the effectiveness of the BNT162b2 and ChAdOx1 vaccines ( 24 ); 3 studies reported the effectiveness of the BNT162b2, ChAdOx1, and mRNA-1273 vaccines ( 12 , 21 , 22 ); 5 studies reported the effectiveness of the BNT162b2, and mRNA-1273 vaccines ( 14 , 16 , 17 , 20 , 23 ); 2 studies reported the effectiveness of the BNT162b2 vaccine ( 18 , 19 ), and 1 study reported the effectiveness of the mRNA-1273 vaccine ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies had a total sample of around one hundred million (N = 148260342) participants and of these, 74.2% were fully vaccinated ( n = 110076947) with at least two-doses of COVID-19 vaccines ( Table 1 ). Among the 13 studies, 1 study reported the effectiveness of the BNT162b2 (Pfizer–BioNTech), ChAdOx1 (AstraZeneca), mRNA-1273 (Moderna) and JNJ-78436735 vaccines ( 25 ); 1 study reported the effectiveness of the BNT162b2 and ChAdOx1 vaccines ( 24 ); 3 studies reported the effectiveness of the BNT162b2, ChAdOx1, and mRNA-1273 vaccines ( 12 , 21 , 22 ); 5 studies reported the effectiveness of the BNT162b2, and mRNA-1273 vaccines ( 14 , 16 , 17 , 20 , 23 ); 2 studies reported the effectiveness of the BNT162b2 vaccine ( 18 , 19 ), and 1 study reported the effectiveness of the mRNA-1273 vaccine ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…Note that the vaccination rate of BNT162b2 in Japan is approximately 90%. Furthermore, based on the waning immunity for infection protection, s was defined as 0.24 to match the model [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…39 In 20% of individuals, T cell reactivity to the Omicron spike is lowered by more than 50%. 40 The majority of Omicron epitopes are sequence conserved and preserve affinity to HLA-I. 41 In some cases, the immune response against SARS-CoV-2 may be dysregulated, leading to a severe hyperinflammatory condition, CRS.…”
Section: Immunopathogenesis Of Omicronmentioning
confidence: 99%
“…Shortly after the booster immunization, T cell responsiveness to Omicron is improved 39 . In 20% of individuals, T cell reactivity to the Omicron spike is lowered by more than 50% 40 . The majority of Omicron epitopes are sequence conserved and preserve affinity to HLA‐I 41 …”
Section: Introductionmentioning
confidence: 99%